1999
DOI: 10.1200/jco.1999.17.2.651
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Chemotherapy With Interleukin-2 and Interferon Alfa for the Treatment of Metastatic Melanoma

Abstract: A plateau in both the survival and time to progression curves beyond 2 years (15% of the patients) and a greater than 10% disease-free survival beyond 4 years indicate that there may be a long-term benefit for some patients. The limited toxicity of this regimen should permit its use in most oncology settings. A randomized trial of chemoimmunotherapy versus chemotherapy should be performed to establish the value of chemoimmunotherapy for melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
34
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(35 citation statements)
references
References 16 publications
0
34
0
1
Order By: Relevance
“…Recently, a combination of chemo-and immunotherapy has been investigated in several phase II studies (Khayat et al, 1993;Legha et al, 1998;O'Day et al, 1999;Richards et al, 1999) with responses of 40 -60%. However, in a recent phase III trial, survival did not improve with the addition of high-dose IL2 and IFNa to chemotherapy compared to chemotherapy alone (Rosenberg et al, 1999).…”
mentioning
confidence: 99%
“…Recently, a combination of chemo-and immunotherapy has been investigated in several phase II studies (Khayat et al, 1993;Legha et al, 1998;O'Day et al, 1999;Richards et al, 1999) with responses of 40 -60%. However, in a recent phase III trial, survival did not improve with the addition of high-dose IL2 and IFNa to chemotherapy compared to chemotherapy alone (Rosenberg et al, 1999).…”
mentioning
confidence: 99%
“…DTIC) (Dummer et al, 1995) or to IFNα . In the last years, several phase II-trials have focused on biochemotherapy consisting of a combination of several cytotoxic substances with IFNα and IL-2 Proebstle et al, 1998;Richards et al, 1999;Sertoli et al, 1999). Legha and coworkers reported on encouraging tumour responses (21% CR, 43% PR) achieved with biochemotherapy in advanced metastatic melanoma patients .…”
Section: Discussionmentioning
confidence: 99%
“…Complex combinations of cytotoxic drugs with biological response modifiers, such as interferon α (IFNα) and interleukin 2 (IL-2), demonstrated encouraging results in achieving long-lasting tumour responses Richards et al, 1999). A relatively large number (about 10%) of patients with lasting complete remissions will survive for many years.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For theoretical reasons of synergy and in an attempt to improve the efficacy of existing regimens, these agents have been combined with cytotoxic agents. It is unclear whether such combinations offer a therapeutic advance over simpler and less toxic treatments [18][19][20][21][22][23][24][25][26][27][28][29] . A multivariate análisis in patients with disseminated melanoma comparing dacarbacine monochemotherapy versus dacarbacine plus immunotherapy showed that the combination of DTIC and interferon-alpha appears more active than standard singleagent DTIC in metastatic melanoma 30 .…”
Section: Discusionmentioning
confidence: 99%